PENGGUNAAN TERAPI ELEKTROFISIS PADA SATU RUMAH SAKIT UMUM SWASTA DI JAKARTA (Lembaga Penerbitan Universitas Esa Unggul, 2020)
One of the physiotherapy interventions that need to be fulfilled in a hospital is electro physical agents and requires specific electro physical modalities for physiotherapy intervention. Furthermore, electro physical agent therapy is an important component for physiotherapy and consists of the application of various modes of electro physical agents for therapeutic purposes. Research on the use of electro physical agent in hospitals was still very rare. Then, this study purposed to determine the use of electro physical modalities in one hospital as a preliminary study. This study uses a case study at hospital M in the South Jakarta area about the use of electro physical agent modalities. The M hospital has electro physical agent modalities such as Infra-Red Radiation, Micro wave diathermy (MWD), Short wave diathermy (SWD), TENS, Electrical Stimulation, Lasers, ESWT, Cervical & Lumbar Mechanical Traction Equipment, Paraffin Bath and Nebulizer. The most used modalities were Diathermy (MWD and SWD). The next most used are US, TENS and While others electro physical modalities that are rarely used were Nebulizer, IRR, Electrical Stimulation, Mechanical Traction Equipment and Paraffin Bath.